PENGARUH E-SERVICE QUALITY DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PENGGUNAAN PRODUK GOPAY (STUDI PADA PENGGUNA APLIKASI GOJEK DI KOTA SEMARANG) - Danang Kukuh Argitama; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2020)
Increasing competition for e-money, especially business competition in the field of payment services. One payment service that is growing rapidly is Go-Pay, an online payment service that is on the Go-Jek application. The number of Go-Pay users has decreased even though the achievement of the target has increased in its realization but in the percentage of changes, there has been a sharp decline.. The goals of this research are to determine the effect of e-service quality and promotion on using decisions at Go-Pay product. Type of research using explanatory research with data collection technics by interviews and data collection tools using offline questionnaires with a sample of 30 respondents Go-Pay user in Semarang City and using online questionnaires with a sample 70 respondents Go-Pay user in Semarang City using methods of purposive sampling and Accidental Sampling. The analysis technique used validity test, reliability test, cross-tabulation test, simple linear regression, multiple linear regression, t-test, and F test with SPSS 25.0. From the result of research indicate that e-service quality influence to using decision equal to 40,3%, promotion influence to using decision equal to 43,3%, while simultan e-service quality and promotion effect on using decision equal to 55,7%. It means the better the quality of e-service quality and promotion then the higher using decision Go-Pay in Semarang City. The promotion variable to the usage decision variable has a bigger effect than e-service quality. Based on the results of the study, the researcher suggested that aplikasi Karya Anak Bangsa company performs improvements in the Go-Pay transaction system so as not to cause errors when making transactions using Go-Pay, they also increase the security of data privacy of Go-Pay users so that e-service quality of Go-Pay can be increased. That way, Go-Pay can be a priority choice for users in payment.